HUBUNGAN DUKUNGAN KELUARGA DENGAN PERAWATAN DIRI (SELF CARE ACTIVITY) PADA PASIEN DIABETES MELITUS TIPE 2 - Ni Wayan Yatik Marlinda; I Kadek Nuryanto; Ni Ketut Noriani (Jurnal Riset Kesehatan Nasional, 2019)
This study was to determine the correlation between family support and self-care activity in patient with type 2 diabetes mellitus at public health center II west Denpasar. This study employed correlative analytics design with cross sectional study. The population of this study were 131 patients with type 2 diabetes mellitus. There were 99 respondents recruited as the sample of the study which were selected by using non-probability, consecutive sampling technique. The data were collected by using questionnaire and analyzed statistically y using Spearman’s Rho test. The finding of this study showed that there were 59 respondents (56.6%) had moderate family support and 77 respondents (77.8%) had good self-care activity. There was a positive correlation between family support and self-care activity in patient with type 2 diabetes mellitus (p-value = 0.001; r = 0.370). Good family support could affect self-care activity in patients with type 2 diabetes mellitus. Family are expected to motivate patient in carry-out self-care activity. Keywords: Family support, Self-care activity, Type 2 diabetes mellitus